Pluri‐decadal evolution of rock glaciers surface velocity and its impact on sediment export rates towards high alpine torrents. Issue 15 (22nd October 2021) - Kummert, Mario; Bodin, Xavier; Braillard, Luc; Delaloye, Reynald
Abstract: The acceleration of surface velocities observed over the last two decades on monitored rock glaciers worldwide is a widespread signal of the probable control of warming air temperatures on long‐term permafrost creep. Yet, the actual consequences of this acceleration on sediment availability in high mountain catchments have never been properly estimated at the pluri‐decadal scale. The present study evaluates the sediment transfer activity between five rock glaciers located in the western European Alps and the headwaters of the torrential channels they are respectively connected to. It reposes on the orthorectification of aerial images available generally from the 1960s to the mid‐2010, to reconstruct time‐series of (i) horizontal surface velocities and (ii) frontal erosion rates. Values of horizontal velocity are retrieved by tracking the displacement of boulders on the surface of rock glaciers between consecutive images while erosion rates affecting the fronts are calculated by combining these values of displacement with the geometry of the front (mean width and rock glacier thickness) derived from recent high‐resolution digital elevation models. Results confirm the general acceleration of rock glaciers surface velocities since the 1970s and indicate that this accelerating trend is causing an increase in the erosion rates calculated at the front of most studied rock glaciers. In some cases and over specific periods however, the acceleration resulted in the advance of the whole landforms over their own sediments, leading to a comparatively low sediment export towards the torrents. Abstract : Time‐series of aerial images covering roughly the last 55 years are orthorectified and analyzed to derive the evolution of surface horizontal velocities and frontal erosion rates for five rock glaciers known as connected to torrential channels. The acceleration of surface velocities observed since the 1970s was either associated with (i) a gradual advance of the whole landform over its own sediments leading to a comparatively low sediment export downslope or (ii) a gradual increase in the frontal erosion rate.